Finite Element Study on The Effect of Substrate Properties in Micro-cutting Thin Workpiece Materials - Saptaji, Kushendarsyah; Subbiah, Sathyan (IOP Publishing, 2016)
The cutting mechanism and residual stress profile of the micro-cutting thin workpiece are affected by the interaction of the thin workpiece and the fixture (substrate) underneath it similar to that observed in the nano-indentation and nano-scratching of thin film. The appropriate substrate properties are necessary especially to avoid detachment during machining and to minimize deformation and warping of the machined thin workpiece. Thus, the investigations of the influence of substrate properties on micro-cutting thin workpiece are essentially to be conducted. The finite element study of orthogonal micro-cutting of thin Al6061-T6 is presented here. The simulations were conducted to study the residual stress profile across the thickness of the machined thin workpiece at various workpiece thicknesses and various substrate (adhesive) elastic properties. Simulations results show that as the machined workpiece become thinner, the stress is more significant not only on the machined surface but also it can reach the bottom of the workpiece. The stiffer substrate produces less variation of the stress across the workpiece thickness while more compliant substrate produces broader stress variation as the workpiece become thinner. The results show the significant effect of the workpiece thickness and the substrate properties on the stress profiles in the micro-cutting of thin workpiece.